An Investigation into Deep Learning and Machine Learning Approaches for Securing the Internet of Things (IOT) - A. Y. Gital; A. A. Ibrahim; H. Sunusi (International Journal of Integrative Research, 2023)
The study explores machine learning and deep learning (ML) (DL) model helped in solving IoT the computation problem, which led to the adoption of many domains for its application in the problem-solving task. Solving a specific problem, this has led to the idea that deep and machine learning (DL) (ML) are two powerful approaches to data. Therefore, the purpose of this article is to provide a systematic review of “Scanning Machines and Deep Learning Methods for Internet of Things (IOT) Security and Privacy” on the current state of research on IoT and its joint venture with DL. This technique uses discrepancy privacy to prevent the adversary from understanding the use cases used to build the target model. The paper concluded that algorithms deep learning and machine learning were only developed recently and are not intended for use in cryptographic applications. However, for researchers who can implement cryptography, deep learning and machine learning can be used to implement cryptography.